Moderating Effect of Environmental Management Accounting on Innovation and Firm Performance: Review of Contemporary Literature - Saeidi, Sayedeh Parastoo (Asian Research Consortium, 2013)
This paper reviews the effect of EMA on relationship amid innovation and firm performance. Review of literature demonstrates that enhancement and improvement in cost information system through recognition of environmental cost lead to innovate new ways in production, and concurrently increases the sale and number of customers. Based on the findings of literature review, increasing number of customers leads to higher level of financial performance for firms. Therefore, this paper posits a framework that links the moderating effects of EMA on relationship amid innovation and firm performance for future empirification.